2021
DOI: 10.1097/md.0000000000025328
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of double single suture-button fixation, suture-button fixation, and screw fixation for ankle syndesmosis injury

Abstract: Different methods have been used throughout the years for syndesmotic injury but there is no consensus on the ideal treatment. Some methods are expensive and some have more complications. The aim of this study is to compare single suture endobutton with double suture endobutton and screw fixation for syndesmotic injury. Sixty nine patients with syndesmotic injury with fibular fractures whom were treated with a single interosseous suture endobutton system (ZipTight TM , Zimmer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…taking these risks into account, some scholars have attempted to treat inferior tibio bular joint injury by Endobutton plate xation [8][9][10]16,18]. The Endobutton device is a novel inferior tibio bular xation device with a xation strength close to the screw, and the semi-rigid biomechanical properties of the device allow physiological fretting between the lower tibia and bula, thus accelerating ligament healing; no secondary surgery is required to reduce trauma [3,19,21]. Experiments show that there is no risk of screw breakage, no need for routine removal after surgery by Endobutton,and it can better restore ankle function, reduce related complications and other advantages, less trauma [ 16,20].…”
Section: Discussionmentioning
confidence: 99%
“…taking these risks into account, some scholars have attempted to treat inferior tibio bular joint injury by Endobutton plate xation [8][9][10]16,18]. The Endobutton device is a novel inferior tibio bular xation device with a xation strength close to the screw, and the semi-rigid biomechanical properties of the device allow physiological fretting between the lower tibia and bula, thus accelerating ligament healing; no secondary surgery is required to reduce trauma [3,19,21]. Experiments show that there is no risk of screw breakage, no need for routine removal after surgery by Endobutton,and it can better restore ankle function, reduce related complications and other advantages, less trauma [ 16,20].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that it may be useful to first perform an operation with a one-third tubular plate on the fibula and two trans-syndesmotic screws so that the bones can heal properly, with this being replaced at six weeks with a double TightRope to allow full weight-bearing and articulation while avoiding the risk of tibiofibular diastasis and simultaneously allowing the syndesmosis time to repair properly 27 . However, this would inevitably lead to increased costs because of the need for a second surgery 28 . Besides, the double surgery requirement in addition to increased costs, increases the risks associated with anesthesia and combines the possible complications of the two different surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,11 Various fixation techniques have been reported for the repair of syndesmosis, and screws and suture-button devices are the most common fixation methods. 2,3,14 However, several complications of screw fixation, such as screw loosening, breakage, local irritation, and discomfort, are reported for this rigid fixation. 5,18,21,27 Malreduction of syndesmosis has also been noted as a significant problem, and its incidence has been found to be 20.8% to 52% on postoperative CT scans.…”
Section: Introductionmentioning
confidence: 99%